Asymmetric Ene‐Reduction by F420‐Dependent Oxidoreductases B (FDOR‐B) from Mycobacterium smegmatis. (8th March 2023) - Kang, Suk Woo; Antoney, James; Lupton, David W.; Speight, Robert; Scott, Colin; Jackson, Colin J.
Abstract: Asymmetric reduction by ene‐reductases has received considerable attention in recent decades. While several enzyme families possess ene‐reductase activity, the Old Yellow Enzyme (OYE) family has received the most scientific and industrial attention. However, there is a limited substrate range and few stereocomplementary pairs of current ene‐reductases, necessitating the development of a complementary class. Flavin/deazaflavin oxidoreductases (FDORs) that use the uncommon cofactor F420 have recently gained attention as ene‐reductases for use in biocatalysis due to their stereocomplementarity with OYEs. Although the enzymes of the FDOR‐As sub‐group have been characterized in this context and reported to catalyse ene‐reductions enantioselectively, enzymes from the similarly large, but more diverse, FDOR‐B sub‐group have not been investigated in this context. In this study, we investigated the activity of eight FDOR‐B enzymes distributed across this sub‐group, evaluating their specific activity, kinetic properties, and stereoselectivity against α, β‐unsaturated compounds. The stereochemical outcomes of the FDOR‐Bs are compared with enzymes of the FDOR‐A sub‐group and OYE family. Computational modelling and induced‐fit docking are used to rationalize the observed catalytic behaviour and proposed a catalytic mechanism. Abstract : The first investigation of asymmetric ene‐reductions by FDOR‐Bs and exploration of additional ene‐reductase candidates from FDOR family will advance our understanding of FDORs as industrial biocatalysts. Due to their presence in a greater variety of bacterial genera than FDOR‐A enzymes, FDOR‐Bs are expected to offer greater versatility in the search for potent activity against industrially relevant substrates.